Antibiotics self-medication among medical and nonmedical students at two prominent Universities in Benghazi City, Libya - Mohamed F Ghaieth; Sara R. M. Elhag; Mamoun E Hussien; Emad H. E. Konozy (Wolters Kluwer Medknow Publications, 2015)
Background: Trivial use of antibiotics is a major reason for the spread of antibiotics resistance. The aim behind undertaking this investigation was to study the prevalence antibiotics self-medication among university students in Benghazi city. Methods: A questionnaire-based cross-sectional, survey was conducted at both Libyan International Medical University and Benghazi University. A total of 665 copies of questionnaires was distributed. A total of 363 forms were completed and returned (response rate 55%). Remaining responses were either with no antibiotics use history within the past 1 year or were provided incomplete. Results: Among the respondents, 45% were males and 55% females. Males practiced self-medication more compared to females. Approximately, 43% and 46% from medical and nonmedical students, respectively, were antibiotics self-medicated. A total of 153 students (42%) out of total respondents administered antibiotics for symptoms related to respiratory problems, among which 74 students (48%) took antibiotics based on doctor's prescription. Among the respondents, 94 students (27%) who had antibiotics, were covered under medical insurance, and 19 (29%) of the medically insured students had antibiotics without doctor's prescription. About 14% of students did not complete their antibiotics course. Of these, 57% were medical students, and 43% were nonmedical students. The rate of self-medication among higher classes was more as compared to lower classes. About 58% of students overdosed the antibiotic, while 15% had antibiotics for <3 days, for treatment of ailments such as acne, toothache, diarrhea, earache, and tonsillitis. About 75% of students purchased the antibiotics in consultation with a pharmacist. Conclusion: Self-medication is a frequent problem among university students in Benghazi city. There is a need for an immediate intervention to address this malpractice among both students and medical practitioners.